Moderators tirade in viral video transcribed - Malay, Mail (Malay Mail, 2013)
THE MALAY MAIL transcribes the part where a UUM student, K.S. Bawani, was cut off by a moderator at a forum on politics in a video that went viral and caused the setting up of Facebook pages in support of the student.